Women to grow up with: transnational feminism in empowering biographies for girls - Einat Lachover; Shai Rudin (Cogent Social Sciences)
This article examines the case study of Real-Life Legends: 50 Women to Grow Up with in Israel, a local anthology published in 2019 as part of the global trend of women’s biographical collections aimed at empowering girls. Investigating the dissemination of current feminist ideas in global popular culture within a specific cultural context, the study analyzes the selection of featured women, their biographical narratives, and the book’s creation process led by a group of women. The analysis reveals the anthology’s challenges in balancing national identity and feminist values, as Real-Life Legends shifts from the dominant national-Zionist narrative to a universal discourse while retaining a notable militaristic focus. In contrast to the book’s critical stance on its national narrative, the book’s feminist discourse aligns with contemporary global neoliberal discourse, raising questions about its transformative potential. The marginalization of the Israeli feminist movement within the book supports its depoliticization of the feminist cause. However, at the same time, a nuanced radical feminist perspective within the texts reveals an interplay between the private and public domains. This case study contributes to understanding the adaptation of global feminist ideas to specific cultural settings, shedding light on the intersections of gender, nationality, and transnational popular feminism.